A Study of Consumer Perception towards Online Grocery Shopping: Challenges and Prospects - Shukla, Sakshi Mishra (Indian Journal of Computer Science, 2017)
Online shopping is a common phenomenon for todayâ€™s customers even in smaller cities but there are some specific markets that are still facing challenges for growth and opportunities to a large extent. One such market is online grocery shopping segment. The paper studies various dimensions of online grocery shopping ranging from its characteristics, its processes, present consumer perception towards online grocery shopping,Â Indian players in the market, and the different variables around which the study revolves. The research methodology of the paper includes literature review, formulation of a structured questionnaire, survey conducted in the city of Allahabad, Uttar Pradesh, India. The data was analyzed with the help of statistical software SPSS and statistical tools like frequency tables, Factor Analysis etc. The major findings and recommendations of the research paper provided foundation for reasons behind expanding the market of online grocery shopping, the challenges as well as the future business prospects in Tier II. The study concluded that factors like wide variety of products, offers and discounts, free home delivery, time saving and convenience, cost effective, easy terms and conditions, user friendliness, authenticity and genuineness, easy to order and cash on delivery should be taken as strengths and pillars of online grocery shopping and these can be improvised or modified to extract maximum advantage for business.